Struggle and failure on clinical placement: a critical narrative review. Issue 2 (21st November 2017) - Davenport, Rachel; Hewat, Sally; Ferguson, Alison; McAllister, Sue; Lincoln, Michelle
Abstract: Background: Clinical placements are crucial to the development of skills and competencies in speech–language pathology (SLP) education and, more generally, a requirement of all health professional training programmes. Literature from medical education provides a context for understanding how the environment can be vital to all students' learning. Given the increasing costs of education and demands on health services, students who struggle or fail on clinical placement place an additional burden on educators. Therefore, if more is known or understood about these students and their experience in relation to the clinical learning environment, appropriate strategies and support can be provided to reduce the burden. However, this literature does not specifically explore marginal or failing students and their experience. Aims: To review existing research that has explored failing and struggling health professional students undertaking clinical placements and, in particular, SLP students. Methods & Procedures: A critical narrative review was undertaken. Three electronic databases, ProQuest, CINAHL and OVID (Medline 1948–), were searched for papers exploring marginal and failing students in clinical placement contexts across all health professions, published between 1988 and 2017. Data were extracted and examined to determine the breadth of the existing research, and publications were critically appraised and major research themes identified. Main Contribution: Sixty‐nine papers were included in the review. The majority came from medicine and nursing in the United States and United Kingdom, with other allied health disciplines less well represented. The review identified key themes with the majority of papers focused on identification of at risk students and support and remediation. The review also highlighted the absence of literature relating to the student voice and in the allied health professions. Conclusions & Implications: This review highlighted the limited research related to failing/struggling student learning in clinical contexts, and only a handful of papers have specifically addressed marginal or failing students in allied health professions. The complexity of interrelated factors in this field has been highlighted in this review. Further research needs to include the student's voice to develop greater understanding and insights of struggle and failure in clinical contexts.